The planning and experience of time and space in three gestural media: theatre, film and interactive film. (1st January 2012) - Danylak, Roman; Edmonds, Ernest
Human bodily gestures are now clearly present as a factor in human– computer interface design extending interactor experiences into designed space, in particular as interactive film, where the interactor may have gestural and emotional experiences with on-screen material. This paper describes the organisation of time and space in three media forms where gestures are prominent, namely theatre, film and interactive film, showing their interrelation, where interactive film absorbs processes of the first two media and is experienced as a game. The plan processes of the media is the focus of discussion, in particular the plan from the interactive gestural film game, To be or not to be, an original artwork designed and evaluated for practice-based research. A summary of gestural evaluation is also included.